Multimodality Management of Cavernous Sinus Hemangiomas—An Institutional Experience - Srinivas, Dwarakanath; Sarma, Pragyan; Shukla, Dhaval; Bhat, Dhananjay; Pandey, Paritosh; Somanna, Sampath; Chandramouli, Ananthakrishna (Journal of Neurological Surgery Part B: Skull Base, 2017)
Objective Cavernous sinus hemangiomas (CSHs) are benign lesions accounting for less than 2% of the cavernous sinus tumors. They provide a formidable surgical challenge because of their vascularity and their being surrounded by critical neurovascular structures. In this study, one of the largest in available literature, we analyze our experience in the management of these unusual tumors and review the available literature.Materials This is a retrospective analysis of patients who were managed surgically (both microsurgical and Gamma knife radiosurgery [GKRS]) for CSH at our Institution from 2007 to 2015. Complete demographic, clinical-radiologic surgical records were analyzed. Follow-up data were collected from the hospital records.Results Total 23 patients were managed. Among these, 15 patients underwent microsurgery (group 1) whereas 8 underwent GKRS (group 2). Predominant clinical presentation in both the groups included headache and involvement of multiple cranial nerves. Five patients in group 1 had deteriorating vision. The volume of tumors ranged from 29 to 115 cm3 (mean = 64.57 cm3) in group 1 and from 2.1 to 11.6 cm3 in group 2. GKRS was performed with a mean dose of 13 Gy, an average isodose line of 50% with an average coverage of 96%. In group 1, the follow-up period ranged from 6 to 62 months (mean = 29.4 months). The extraocular movement (EOM) preservation rate in our series was not favorable, as most patients presented late with large tumors and established deficits. Recurrence/residual tumor was seen in two cases. In group 2, the follow-up was 5 to 48 months. All of them showed significant reduction in size.Conclusion Both surgery and radiosurgery are highly effective in the management of CSHs. They are complementary to each other, with individual characteristics—the size and volume of the lesion—being the main factors in deciding the choice of treatment.
Keywords: hemangiomas; cavernous sinus; Gamma knife radiosurgery; interdural approach